Intestinal group 1 innate lymphoid cells drive macrophage-induced inflammation and endocrine defects in obesity and promote insulinemia - Rebeca Liébana-García; Marta Olivares; Carlos Francés-Cuesta; Teresa Rubio; Valerio Rossini; Guillermo Quintas; Yolanda Sanz (Gut Microbes, 2023)
ABSTRACTHypercaloric diets overactivate the intestinal immune system and disrupt the microbiome and epithelial cell functions, impairing glucose metabolism. The origins of this inflammatory cascade are poorly characterized. We investigated the involvement of intestinal proinflammatory group 1 innate lymphoid cells (ILC1s) in obesity progression and metabolic disruption. In obese mice, we studied longitudinally the ILC1s response to the diet and ILC1s depletion to address its role in obesity. ILC1s are required for the expansion of pro-inflammatory macrophages and ILC2s. ILC1s depletion induced the ILC3-IL-22 pathway, increasing mucin production, antimicrobial peptides, and neuroendocrine cells. These changes were translated into higher gut hormones and reduced insulinemia and adiposity. ILC1s depletion was also associated with a bloom in Akkermansia muciniphila and decreases in Bilophila spp. Intestinal-ILC1s are upstream activators of inflammatory signals, connecting immunity with the microbiome, the enteroendocrine system, and the intestinal barrier in the control of glucose metabolism and adiposity.